Ethnic Propaganda, Hate Speech, and Mass Violence in Igbo-Hausa/Fulani Relations in Postcolonial Nigeria - James Olusegun Adeyeri and Jackson A. Aluede (University of Johannesburg, 2021)
Opinions are divided on the conduct and nature of the 1967–70 Nigerian civil war, occasioned partly by the Igbo secession and declaration of the Republic of Biafra. Some believe that the Nigerian government adopted a genocidal war strategy characterised by mass violence against civilians, aggressive blockade of the eastern region, artificial famine, and hateful/threatening utterances by many military commanders, accompanied by about one million civilian casualties. On the other hand, some are of the view that the actions of some Nigerian military officers and men were not in consonant with the position of the Nigerian government during the war, but were influenced by their animosity towards the Igbo. In post-civil war Nigeria, Igbo-Hausa/Fulani relations and political discourses are increasingly tense and indicative of a fearful resurgence of mass violence due to prevalent lies, propaganda, and misrepresentations –verbally, on paper, and online/on social media – particularly among the youths on both sides. This paper argues that the historical crisis-ridden relations between the Igbo and the Hausa/Fulani, the attendant 1966 mass killings of Igbos in the north, the nature of the war strategies of the federal government during the civil war, and the currently mounting tension are all direct results of contending ethnic propaganda including hate speech, lies, and name-calling in a bid to gain political and strategic advantages over other ethnic groups. Thus, this paper is a historical inquiry into the role of propaganda and hate speech in socio-political interactions, discourses, and incitements of mass violence among the heterogeneous Nigerian population, particularly the Igbo and the Hausa/Fulani. The paper proposes legislative, constitutional, and active citizenship advocacies to address the menace. The article utilises primary and secondary sources to analyse and interpret the subject-matter of the paper.